An Atypical Presentation of Pityriasis Rosea Localized to the Extremities - Daze, Robert P (Cureus, 2020)
Pityriasis rosea (PR) is a benign, self-limiting, papulosquamous disorder characterized by the onset of a herald patch followed by an abrupt eruption of multiple salmon-colored papules and plaques on the trunk and proximal extremities. The individual lesions are often outlined by a collarette of scale and are distributed along the lines of cleavage. While many authors acknowledge an etiologic association with human herpesvirus 6 and human herpesvirus 7, thereby suggesting a viral exanthem, the exact cause remains unclear. While typically demonstrating a truncal predilection, this presentation may be absent in some patients who instead exhibit atypical features and distributions. Various clinical variants include papular, vesicular, purpuric, and eczematoid. The condition rarely manifests without truncal involvement and localized only to the distal extremities. We present a unique case report of a 65-year-old-male with biopsy-proven PR that was localized to his distal extremities with a clinical absence of truncal involvement.